Prenuptial Agreement in Islamic Family Law: A Maqāṣid al-Sharī‘ah Approach - Khairul Mufti Rambe (Faculty of Law, Universitas Pekalongan, 2025)
This study analyzes prenuptial agreements within the framework of Islamic family law and explores their harmonization with contemporary social demands. While recognized under Article 29 of Law No. 1 of 1974 jo. Law No. 16 of 2019, such agreements remain contested in classical Islamic jurisprudence. Using a qualitative method with a normative-conceptual and comparative approach, this research draws from classical texts (e.g., al-Māwardī, Ibn Qudāmah) and contemporary thought on maqāṣid al-sharī‘ah (e.g., al-Shāṭibī, Ibn ʿĀshūr), as well as interviews with scholars and practitioners. The findings show that prenuptial agreements are not inherently in conflict with Islamic law if aligned with core marital principles. When framed within maqāṣid, they can promote maṣlaḥah by clarifying spousal rights and protecting shared assets. The academic contribution of this study lies in its integrative framework that bridges traditional Islamic legal doctrine with the evolving socio-legal context of Muslim societies. It also offers practical implications for developing Islamic-compatible prenuptial models and raising public awareness